Immunological Perspectives of Leishmaniasis - Nylén, Susanne (Medknow Publications, 2010)
Leishmania parasites have been widely used in experimental models to understand generation, maintenance and failure of immune responses underlying resistance and susceptibility to infection. The clinical outcomes of Leishmania infection depend on the infecting species and the immune status of the host. Noticeably most people exposed Leishmania never develop overt disease. Understanding the immunological events that result in failure or successful control of the parasites is fundamental to both design and evaluation of vaccines and therapies against the leishmaniases. Recent studies visualizing immune response to Leishmania major in the skin have given new insights into the different immune cells acting as hosts the parasite during different stage of infection. Control of Leishmania infection and disease progression has been associated with generation of T-helper (Th) 1 and Th2 responses respectively. Though still valid in several aspects, the Th1/Th2 paradigm is an oversimplification in need of revision. Th2 polarization has never explained severity of human leishmanial disease and a number of other T-cell subsets, including regulatory T- and Th17- cells, have important roles in susceptibility and resistance of both experimental and human leishmanial disease. This review gives an updated overview of immunological response considered to be of importance in protection, susceptibility, disease progression and cure of leishmaniasis, with a special emphasis on human diseases.